2022
DOI: 10.1136/heartjnl-2021-320768
|View full text |Cite
|
Sign up to set email alerts
|

Fractional flow reserve versus angiography alone in guiding myocardial revascularisation: a systematic review and meta-analysis of randomised trials

Abstract: BackgroundRandomised trials evaluating the efficacy and safety of fractional flow reserve (FFR)-guided versus angiography-guided revascularisation among patients with obstructive coronary artery disease (CAD) have yielded mixed results.AimsTo examine the comparative efficacy and safety of FFR-guided versus angiography-guided revascularisation among patients with obstructive CAD.MethodsAn electronic search of MEDLINE, SCOPUS and Cochrane databases without language restrictions was performed through November 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Two previous meta-analyses included 5094 patients from 7 RCTs [ 13 ], and an analysis from 5 RCTs totalling 2288 patients [ 14 ]. Both of these meta-analyses [ 13 , 14 ] found no difference in mortality when FFR-guidance was compared to angiography-guidance for complete revascularisation. However, our study also includes FRAME-AMI [ 3 ], only recently reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous meta-analyses included 5094 patients from 7 RCTs [ 13 ], and an analysis from 5 RCTs totalling 2288 patients [ 14 ]. Both of these meta-analyses [ 13 , 14 ] found no difference in mortality when FFR-guidance was compared to angiography-guidance for complete revascularisation. However, our study also includes FRAME-AMI [ 3 ], only recently reported.…”
Section: Discussionmentioning
confidence: 99%
“…We also excluded the RCT by Quintella et al [ 15 ] (n = 69), which was included in the previous meta-analysis [ 14 ], and the DEFER-DES trial [ 16 ] (Fractional Flow Reserve to Determine the Appropriateness of Angioplasty in Moderate Coronary Stenosis), which was included in the larger prior meta-analysis [ 13 ], as they used an FFR threshold of <0.75. Furthermore, we excluded the DK-CRUSH VI trial (Double Kissing Crush Versus Provisional Stenting Technique for Treatment of Coronary Bifurcation Lesions) [ 17 ], which was included in the larger prior meta-analysis [ 13 ], as only the side branch involved in a provisional bifurcation stenting strategy was randomised to either FFR-guided or angiography-guided revascularisation, rather than the lesion in the main vessel. Furthermore, we took care to only include patients with obstructive CAD from the RIPCORD-2 trial [ 4 ], to better reflect current clinical practice of when FFR use would be considered, which was not the case in the previous meta-analysis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Elbadawi et al present a literature-based meta-analysis of randomised controlled trials that studied the outcome of FFR-guided compared with angiography-guided PCI 3. They include more recent trials, longer term follow-up data from early trials and trials that focused on patients with acute coronary syndromes.…”
mentioning
confidence: 99%
“…In summary, the value of using FFR over angiographic appearance alone to guide revascularisation was questioned by longer term outcome data summarised in a meta-analysis by Elbadawi et al 3. Given the major impact of coronary heart disease on QOL, it is vital to consider and value patient-centred outcomes alongside MACE.…”
mentioning
confidence: 99%
“…A systematic review and meta-analysis of the use of fractional flow reserve (FFR) for guiding myocardial revascularisation5 that included seven trials with 5094 patients concluded that FFR-guided revascularisation, compared with angiography alone, resulted in implantation of fewer stents but did not affect the risk of long-term adverse cardiac events. In the accompanying editorial, Somaratne6 argues that patient-centred outcomes, not just major adverse events, are important and suggests that selective treatment of coronary lesions based on FFR may relieve symptoms and improve quality of life.…”
mentioning
confidence: 99%